2021
DOI: 10.1590/1678-4766e2021024
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the diet of Arctocephalus gazella (Pinnipedia), at two localities of the South Shetland Islands, with emphasis on the fish component

Abstract: We studied the diet of non-breeding male Antarctic fur Seals Arctocephalus gazella (Peters, 1875) at two different localities of the South Shetland Islands: Stranger Point, King George Island/Isla 25 de Mayo and Duthoit Point, Nelson Island, by the analysis of 65 faecal samples collected in February 2012. Overall, Antarctic krill Euphausia superba (Dana, 1850) and fish were the main prey taxa followed by penguins and cephalopods. Myctophids were dominant among fish; Gymnoscopelus nicholsi (Gilbert, 1911) was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The total sh lengths estimated in this work showed that A. gazella preyed upon mature stages of P. antarctica and E. antarctica and immature stages of G. nicholsi and C. wilsoni. Similar sh ontogenetic stages were represented in the diets of fur seals from different colonies of the South Shetland Islands and the Antarctic Peninsula (Casaux et al 2003a(Casaux et al , 2003bOsman et al 2004;Descalzo et al 2021). P. antarctica inhabits pelagic waters over and near the bottom of the Antarctic continental shelf (Gon and Heemstra 1990; Pinkerton 2017).…”
Section: Resultsmentioning
confidence: 69%
“…The total sh lengths estimated in this work showed that A. gazella preyed upon mature stages of P. antarctica and E. antarctica and immature stages of G. nicholsi and C. wilsoni. Similar sh ontogenetic stages were represented in the diets of fur seals from different colonies of the South Shetland Islands and the Antarctic Peninsula (Casaux et al 2003a(Casaux et al , 2003bOsman et al 2004;Descalzo et al 2021). P. antarctica inhabits pelagic waters over and near the bottom of the Antarctic continental shelf (Gon and Heemstra 1990; Pinkerton 2017).…”
Section: Resultsmentioning
confidence: 69%